Modernising state-level regulation and policies to boost mobility in the United States - Sutherland, Douglas (OECD Economics Department Working Papers, 2020)
The U.S. population is becoming increasingly urban and has gradually shifted to the south and west. Policy restrictions have played a role in preventing dynamic areas expanding, and when they do expand it can be through low-density housing sprawl. Land use restrictions and a sluggish housing supply as well as difficulties in making timely and co-ordinated supply of infrastructure have hindered workers benefiting from new opportunities including through moving. Policies can address these issues by targeting housing affordability, help families move and invest in infrastructure to improve accessibility and connectivity